Esophageal squamous cell carcinoma with colonic and rectal metastases: a rare case report - Yang, Jianquan; Guo, Wen; Pang, Xuezhou; Tang, Yuerong; Zhang, Yakun; Zeng, Beilei; Gui, Yan; Ma, Daiyuan (Frontiers in Oncology, 2025)
As a common malignant tumor, esophageal cancer is easy to relapse and distant metastasis, and the prognosis is very poor. Colon and rectal metastasis of esophageal cancer is extremely rare. This study reports a case of colorectal and rectal metastasis in an esophageal squamous cell carcinoma patient. The patient was a 65-year-old man who presented with progressive swallowing obstruction. Gastroscopy and pathological biopsy revealed low-differentiated squamous cell carcinoma in the lower esophagus (32cm from the incisor). After completing the relevant examination, the patient was evaluated by the thoracic surgeon and showed no indication of surgery. Then the patient was received 2 cycles of Abraxane plus cisplatin with Sintilimab. After the treatment, the esophageal lesion was examined by Chest CT, and assesses again by the surgeon again and radical radiotherapy was recommended without indication of surgery. After radiotherapy, the patient underwent comprehensive imaging examination. Abdominal CT showed mass in the lower abdomen. Colonoscopy and pathological biopsy showed squamous cell carcinoma of colon and rectum. According to the pathological type and tumor monism, and communication with the pathologist, the patient was diagnosed to be esophageal cancer with rectal and colon metastasis. Through this case report, we hope to deepen the understanding of rare esophageal squamous cell metastasis, and comprehensive examination should be conducted before initial treatment to evaluate the tumor status.